2011
DOI: 10.1007/s11764-011-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Structuring survivorship care: discipline-specific clinician perspectives

Abstract: Introduction-Several models for survivorship care are prominent within the cancer literature; however, there is little empirical research that examines what oncology clinicians perceive to be the best approach to caring for cancer survivors, what services survivorship programs should include, and how prepared they feel to care for cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…Some researchers have suggested that the response to these varying interpretations is to develop a universally accepted definition of cancer survivorship based on the premise that the lack of a formal definition impacts the point at which patients are offered survivorship-specific care [23]. Our view differs: we feel that service provision should depend upon individual characteristics such as cancer type, stage, treatment, and individual preferences for follow-up and not a specific temporal window.…”
Section: One Proposed Solutionmentioning
confidence: 99%
“…Some researchers have suggested that the response to these varying interpretations is to develop a universally accepted definition of cancer survivorship based on the premise that the lack of a formal definition impacts the point at which patients are offered survivorship-specific care [23]. Our view differs: we feel that service provision should depend upon individual characteristics such as cancer type, stage, treatment, and individual preferences for follow-up and not a specific temporal window.…”
Section: One Proposed Solutionmentioning
confidence: 99%
“…CCS are usually transitioned to this unit when they are aged over 18 years and off-therapy for at least 5 years. The choice to transfer the follow-up from a pediatric to an adult environment follows the trend of international literature (11,14,15) because of the availability of diagnostic services and consultants more suitable to the patient's age. Furthermore, transition into an adult-focused care may have a beneficial effect on the psychological growth and development of the patients, who, in most cases, seem to be heavily dependent on their parents before transition (16).…”
Section: Introductionmentioning
confidence: 99%
“…15 Thus, in the United States (US), Europe, Australia and Canada a number of new models for adult survivors are being implemented and evaluated. 10,16-19 Each has a different approach based on the patient population, type of follow-up and type of provider. In some institutions and practices, the clinic is disease-specific, such as a breast cancer survivor clinic.…”
Section: The Evolution Of Models Of Carementioning
confidence: 99%